The search of people's luggage - Staicu, Florin (Eximia, 2023)
The police as a public institution is the link between the rule of law and citizens, contributing to building a cooperation with the population, local authorities, the business environment, non-governmental organizations, etc., in order to create a climate of public security. In order to fulfill the constitutional role of the lawyer and public order in Romania, the police as a public institution needs the support of the citizens in whose service it is, and for a good relationship with the community, a good collaboration with it and trust on both sides is necessary. Research on police activity in the field of social control has shown, as a rule of law, that the activity of the police as a state institution has a modest impact on reducing the level of crime and the security of individuals. An increase in the number of police officers does not always lead to a reduction in the crime rate or an increase in the number of cases solved. Factors from the social environment, such as income, unemployment, population structure and education, are the most important elements of the problem that must be taken into account when cataloging the criminal phenomenon. Some analysts believe that police patrols and patrol activities, even double or triple, have a major impact on crime, victimization and public opinion of the police service and how it is applied in everyday life. Changing the phenomenon, the evolution or the reform that the police institutions of different countries have proposed, the idea of "local police" is a common theme that has become the object of numerous studies and statistics that have the main purpose of improving the activity to respond to the possibilities of society in the most efficient way possible. The idea behind this concept is due to the fact that the means of police action as a public institution that helps citizens, become ineffective in dissolving crime and social unrest, which has a negative impact on the institution meant to serve communities.